Clinical Insights into Tubercular Tenosynovitis: A Series of Eight Compound Palmar Ganglion Cases - Esa Gokulakrishnan; Prem K Kothimbakkam; Bharath Vadivelkumar; Vijayashankar Murugesan (Journal of Orthopedics and Joint Surgery)
Chronic flexor tenosynovitis of the wrist is often associated with tuberculosis in developing countries as opposed to rheumatoid arthritis in developed countries. A case series of compound palmar ganglion (eight cases) mimicking flexor tenosynovitis, for which magnetic resonance imaging (MRI) revealed conclusive evidence of cystic swelling and melon seed bodies. Early identification, meticulous surgical excision, and the initiation of appropriate antitubercular therapy are of utmost importance.